Weather forecasts become more important for reducing mortality as the climate warms - Jeffrey G. Shrader; Stephan Thies; Laura Bakkensen; Manuel Linsenmeier; Derek Lemoine (Proceedings of the National Academy of Sciences, 2026)
Climate change will increase the frequency and severity of extreme heat, which is a leading cause of weather-related mortality. We combine causal estimates of how temperature forecast accuracy affects mortality in the United States with expert projections of changes in forecast accuracy over the coming century. Our analysis shows that improving short-run temperature forecasts in line with central expert projections would reduce annual heat-related mortality by about 18% by 2100, saving thousands of lives per year. If investments in earth observation networks and weather models improve forecasts in line with optimistic expert projections, annual heat-related mortality would fall by around 25% by 2100. Improving forecasts facilitates adaptation to climate change, saving more lives when climate change is more severe.